Implementation of 128 bits Camellia Algorithm for Cryptography in Digital Image - Bagus Satrio Waluyo Poetro (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Nowadays information technology requires stronger cryptographic algorithms. Camellia algorithm is also known for its suitability in terms of the implementation of both software and hardware as well as a high level of safety. The digital image is an image f (x, y) which having the spatial coordinates, and brightness levels are discrete. Unlike text messages, the image data has special features such as high redundancy and a high correlation between pixels. This research conducted a cryptographic process of the digital image using the Camellia algorithm. Comparisons were made on three digital image format .bmp, .jpg, .png with 128 bits key block Camellia algorithm. Results shows that Camellia cryptographic algorithms in digital image can successfully produce encrypted images. In addition, the same algorithm can also reproduce the image when decryption process.